(untitled) (Boston, 2015)
Introduction to Agricultural Economics, Sixth Edition, provides readers with a systematic introduction to the basic economic concepts and issues impacting the U.S. food and fiber industry and offers strong coverage of macroeconomic theory and international trade.
Keywords: Agriculture,Nông nghiệp; Economic aspects,Khía cạnh kinh tế; United States,Hoa Kỳ